Development and Validation of a Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC) Method for Identification, Assay and Estimation of Related Substances of Ivermectin in Bulk Drug Batches of Ivermectin Drug Substance. (17th September 2021) - Zhao, Daoli; Wimalasinghe, Rasangi M; Wang, Lin; Rustum, Abu M
Abstract: A reversed-phase high-performance liquid chromatography (RP-HPLC) method has been developed and validated for the identification and assay of Ivermectin, including the identification and estimation of its process-related impurities and degradation products in bulk drug substance of Ivermectin. Analytes were separated on a HALO C18 column (100 mm × 4.6 mm I.D., 2.7 μm particle size) maintained at 40 °C (column temperature) with gradient elution. All analytes of interests were adequately separated within 25 min. All degradation products, process-related impurities and assay were monitored by ultraviolet detection at 254 nm. The new HPLC method described here successfully separated an isomer peak of the active pharmaceutical ingredient (API) from the major API peak. This newly separated isomer peak is around 1.2 to 1.5% (peak area) in typical API samples, and coelutes with the major API peak by all current HPLC methods. Quantitation limit of the HPLC method is 0.1% of target analytical concentration ( 1.0 μg/mL). This method has been demonstrated to be accurate, robust, significantly higher degree of selectivity compared to the HPLC methods of Ivermectin drug substance reported in the literature and in the compendial HPLC methods prescribed in the current USA and European Pharmacopeia.